PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI DI PT DAVIDI INTERNATIONAL BALIKPAPAN KALIMANTAN TIMUR - Tewu, Deandra Sarah Lidya Agatha (Universitas Katolik Parahyangan, 2024)
This study aims to identify the impact of compensation on employee performance at PT. Davidi International. A decline in the performance of production employees is indicated by delays in project execution and poor attendance discipline. Changes in the company’s compensation policy are suspected to be the cause of this decline. This study employs a quantitative method with a descriptive approach, collecting data from 70 production employee respondents through questionnaires. The data were analyzed using simple linear regression with the aid of Microsoft Excel and IBM SPSS 27. The analysis results indicate that both compensation and employee performance fall into the poor category, with average scores of 2.32 and 2.42, respectively. Simple linear regression reveals a positive and significant effect of compensation on performance with a contribution of 74,4%. Improved compensation leads to enhanced employee performance.